NILAI PENDIDIKAN ISLAM NUSANTARA DALAM TRADISI PASAR MALAM JUMAT PAHING DI DESA MENGGORO KECAMATAN TEMBARAK KABUPATEN TEMANGGUNG - Fadli, Muhammad Ulfi (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
Javanese tradition will always be associated with rituals. However, rituals that have the value of Islamic education in the archipelago will be useful as the spread of islam. Likewise, this research is about the educational values of Nusantara Islam in the tradition of the Friday Pahing night market in the village of Menggoro. The purpose of this study is to find the educational values of Nusantara Islam by first knowing the background of tradition, then the rituals that axist in the tradition. The process of collecting data is done by nterviewing various sources needed in the research.Â The material from the interviews obtained and study show that in the friday night market tradition, there are values of Islamic education in the archipelago, namely historical, religious, and moral values. The pahing Friday night tradition teaches ethics so that it is not easy to judge someone by what they see, then makes us aware to always remember and be grateful to Allah SWT, realize that we are in a temporary world, so we must remember death it also reminds people to give money to charity. This research is important to do in the field of traditions that have existed for a long time and experience, especially in the Islamic tradition.Â